Proposal of an assessment tool to diagnose industrial symbiosis readiness - Agudo, Fabiana Liar; Bezerra, Bárbara Stolte [UNESP]; Paes, Luis Alberto Bertolucci [UNESP]; Gobbo Júnior, José Alcides [UNESP] (Elsevier, 2022)
This paper aims to present an original assessment tool developed to diagnose industrial symbiosis (IS) readiness. It is expected that industries with greater symbiotic readiness are more likely to have success in implementing a circular business model. A bibliographic analysis was conducted in order to identify the IS variables and dimensions, mentioned in the literature, as necessary for implementation of a circular business model. Two dimensions were defined in this study: (i) exchange resources and (ii) exchange capacity. The exchange resources dimension diagnoses the company's ability to have the necessary exchange resources to IS implementation (water, energy, by-products, and waste). The exchange capacity dimension diagnoses the company's enabler factors to IS implementation (trust, information, access conditions, and infrastructure). After the definition of dimensions and their respective variables, an assessment tool to diagnose industrial symbiosis readiness was developed. The assessment tool is presented as a checklist format - Symbiotic Readiness Checklist (SRC). This was applied to six co-located industries in the State of São Paulo (Brazil). The proposed SRC could be used to: (a) diagnose the readiness of companies or organizations to implement industrial symbiosis; (b) be a tool in enterprise or organizational strategic planning; (c) assist the development of mechanisms to measure the number of resources consumed and waste produced in the supply chain; (d) assess the circularity of resources.
Keywords: Assessment Tool; Industrial Ecology; Resources Circularity; Sustainability; Symbiosis Readiness